p53 - Prognostic factor of malignant transformation of barrett's esophagus - Aujesky, Rene R; Hajduch, Marian; Neoral, Cestmir; Kral, Vladimir; Lubusska, Lucie; Bohanes, Tomas; Klein, Jiri; Vrba, Radek; Drac, Petr (Biomedical papers, 2005)
The most significant precancerosis in the esophageal cancer is Barrett's esophagus. The risk of malignant transformation is determined primarily in accordance with the degree of dysplastic alterations of the mucosa. Indication of "preventive" extirpation of the esophagus should be supported by other factors, for example by detection of p53 mutation or expression. The study reports on the evaluation of a group of 20 patients with Barrett's esophagus treated at the 1st Department of Surgery, the p53 level and its correlation with histological findings evaluated in these patients. A good correlation was found between the grade of Barrett's esophagus dysplasia and high p53 positivity. This correlation was also confirmed by detection of early carcinoma in patients with "preventive" extirpation of the esophagus due to a high-grade dysplasia. Preliminary results show that examination of p53 level in specimens taken from the esophageal mucosa may be helpful for the estimation of malignant potential of the dysplastic mucosa.
Keywords: Keywords: Esophagus/Esophageal cancer/p53/Barrett's esophagus